Bringing politics into the nursery: early childhood education as a democratic practice (Psicologia USP, 2009)
This paper explores the possibility that early childhood institutions can be, first and foremost, places of political practice - and specifically of democratic politital practice. The case for the primacy of democratic political practice in early childhood institutions is made more urgent by two visible developments in many countries today: the growth of political interest in early childhood education, leading to an expansion of services, and the need to revitalize democratic politics. As well as bringing democratic practice into the nursery, what this would mean and what conditions might enable it, the paper also considers democratic practice at other levels: not only the institutional one but also the national or federal, the regional and the local, and how each level can create democratic spaceat other levels. The paper ends by considering four issues related to democracy in early childhood education, including paradigmatic diversity and the European level.